Comparative Analysis of Students' Science Process Skills Using Virtual Laboratory in Photoelectric Effect Experiments - Nadiyyah, Khoirotun; Aprianti, Rika; Nisa, Uliya Khoirun (U-Teach: Journal Education of Young Physics Teacher, 2025)
The use of virtual laboratories in distance learning has increasingly developed as a solution to overcome the limitations of physical laboratory access, particularly in fostering students' science process skills. This study aims to analyze students' science process skills in a photoelectric effect experiment using two virtual laboratories: PhET Simulation and Amrita VLab. The research method employed is quantitative descriptive analysis, Microsoft Excel (the analysis Toolpak, Pivot table, and Pivot chart), involving physics education students as respondents. Data were collected through an assessment of science process skills based on 13 indicators and the effectiveness of the virtual laboratories across 8 aspects, which were then analyzed using descriptive statistics. The results indicate that observation skills scored the highest (91.56%), while analytical skills received the lowest score (71.56%). In terms of effectiveness, PhET Simulation excelled in supporting conceptual understanding, while Amrita VLab provided a more realistic experimental experience. These findings suggest that virtual laboratories are effective in enhancing students' science process skills in different contexts, depending on the learning objectives